Financing constraints, internal control quality and cost stickiness - Chen, Yufeng; Ma, Yanbai (Journal of Business Economics and Management, 2021)
Managers think that retaining resources is more effective than rebuilding resources after exhausting them. However, financing constraints have brought great uncertainty to this resource decision-making implemented by managers. Data of manufacturing listed firms in China from 2009 to 2017 are used here to explore the impact of financing constraints on cost stickiness. This paper finds that internal financing constraints have a significant promoting effect on cost stickiness, while debt financing constraints and equity financing constraints have a significant restraining effect on cost stickiness. The internal control quality has a moderation effect on this relationship. In a firm with low quality of internal control, internal financing constraints can enhance cost stickiness, but the weakening effect of external financing on cost stickiness is not affected by internal control quality.